ANALISA PENGARUH INTERFERENSI TERHADAP AVAILABILITY PADA JARINGAN TRANSMISI MICROWAVE MENGGUNAKAN SOFTWARE PATHLOSS 5.0 STUDI KASUS DI PT. ALITA PRAYA MITRA - Alfin Hikmaturokhman; Eka Wahyudi; Hendri Sulaiman (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2014)
In doing microwave transmission interference and attenuation effects , not so much propagation Line Of Sight. Therefore it takes a computation and checking of a transmission network that values ??of interference does not greatly effect the availability value is supposed to be, there are several ways to avoid or even eliminate interference case is to replace the sub-band and change the polarization of the antenna system microwae. On the transmission network owned by Axiata PT.XL Banten there is a case of interference, namely the link Panimbang Hop-Labuan-Cigeulis due to using the same frequency and the same sub-band. RF Scanning seen from the results that the link is indeed indicated interference. Therefore, by using software pathloss 5.0 will be able to do an analysis of a link or network terinterferensi. so as to reduce and resolve a case interference occurs, and the value of a link availability can be well worth it. Optimization is done there will be a change of the ODU or replace the antenna polarization between vertical or horizontal. Optimization to do is replacing frequency channel that was using 1h (high) - 1l (low) the frequency is 7747.70 MHz-8059, 02 MHz, to frequency channel 3h (high) - 3l (low) the frequency is 7807.00 MHz-8118.32 MH. By doing this method interference value will be lost. Then after the optimization of the value of availability to 99.99993%.